Falling short of expectations: the 2012 children amendment, from drafting to referendum. Issue 2 (2nd April 2016) - O'Mahony, Conor
ABSTRACT: In November 2012, the Irish electorate approved a new provision in the Constitution dedicated to children's rights. The popular portrayal of the referendum campaign was that it was largely uncontroversial, albeit with a sting in the tail. However, this over-simplifies the reality of a political struggle that was vigorously contested for almost a decade before the actual referendum campaign. While the idea of a children's rights amendment was never far from the political agenda during this period, the political appetite for ambitious reform ebbed and flowed. The campaign itself was successful in passing the amendment, but the outcome was nonetheless seen as a disappointing one. This paper will explore two questions regarding the genesis and evolution of the children amendment, from initial public consultations through to the referendum campaign. First, what were the political forces that sought to influence the wording of the amendment, and which side had more reason to be pleased with the final product? Second, what were the factors that caused the referendum campaign to play out in such an unsatisfactory way for the Government?